Exploring Students’ Conceptual Understanding of Newton’s Law in Senior High School - Devi Ayu Nur'aini; Sandi Danar Cynthia Sari; Siti Nurasiah; Reva Amelia; Helsa Putri Pratama; Desy Nurfiyasari (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study aims to explore high school students' understanding of Newton's laws of motion. The research method used is qualitative descriptive, with data collection through a two-tier diagnostic test. The instrument not only measures correct answers but also explores the reasons behind students' choices. Data analysis was conducted by dividing students' understanding into four categories: (1) Understanding the concept; (2) Misconception; (3) Not understanding the concept; and (4) Guessing. The results showed that students understood the concept of changes in velocity due to changes in the direction of force, with 56.2% of students understanding the concept. The largest misconception was found in the subtopic of Newton's Third Law, which reached 68.5%. Meanwhile, the percentage of students who did not understand the concept was lower than that of students who had misconceptions in all subtopics. These findings confirm that the majority of students did not understand the concept, but had initial understandings that were unscientific or inappropriate. Therefore, teachers need to prepare learning strategies that are not only informative but also reinforce concepts.